Relevance of Diabetes Mellitus, Epidemiological Situation, and Clinical-Morphological Features in Uzbekistan - Allaberdiev , B.T.; Akhrorova , A.B. (Морфологія / Morphologia / Morfologìâ, 2026)
Background. Diabetes mellitus (DM) is one of the most prevalent chronic endocrine disorders worldwide and is characterized by persistent hyperglycemia and the development of microvascular and macrovascular complications. Despite the increasing global burden of the disease, data on the clinical and morphological characteristics of diabetes in Central Asian countries, including the Republic of Uzbekistan, remain limited. Objective. To analyze the clinical and morphological features of diabetes mellitus in patients from the Republic of Uzbekistan and to assess the relationship between histopathological changes and clinical manifestations of the disease. Methods. A cross-sectional descriptive study was conducted involving 230 patients with type 1 and type 2 diabetes mellitus observed between 2022 and 2024. Clinical, biochemical, and instrumental parameters were evaluated, including glycemic con-trol, HbA1c levels, renal function, and ophthalmological status. Morphological analysis was performed on tissue samples of the pancreas, kidneys, and retina obtained from autopsy material and ante-mortem renal biopsies. Standard his-tological staining techniques and morphometric analysis were applied. Statistical analysis included comparative and correlation methods. Results. Poor glycemic control (HbA1c > 7%) was observed in 92.2% of patients. Morphological examination revealed degeneration of pancreatic β-cells with fibrotic replacement, pronounced glomerulosclerosis, and characteristic features of diabetic retinopathy, including retinal neovascularization. The severity of morphological changes showed a significant correlation with disease duration and HbA1c levels (p < 0.01). A substantial proportion of patients demonstrated combined involvement of multiple target organs. Conclusion. Diabetes mellitus in the Republic of Uzbekistan is associated with marked clinical and morphological alterations closely related to inadequate glycemic control and longer disease duration. These findings highlight the importance of early diagnosis and optimization of therapeutic strategies to prevent the prog-ression of diabetic complications.